Pengaruh Financial Literacy, Return dan Resiko terhadap Keputusan Investasi Generasi Milenial Islam di Kota Bekasi - Ari Sulistyowati; Muhammad Richo Rianto; Milda Handayani; Eri Bukhari (ITB AAS INDONESIA Surakarta, 2022)
This study was used to measure the effect of financial literacy, return, and risk on the investment decisions of Islamic millennial generation of Bekasi City. This research is quantitative research where the object used is the Islamic millennial generation in Bekasi City. The number of samples used in this study was 130 respondents. Data collection techniques using questionnaires and data processing and hypothesis testing using SmartPLS 3.0. The results of this study explain that the financial literacy variable has a positive effect on the investment decisions, the return variable has a positive effect on the investment decisions and the risk variable has a positive effect on the investment decisions.